Cytotoxicity of Ciprofloxacin and Steroids in Mouse Tympanic Membrane Fibroblasts. (16th January 2018) - Redula, Sonny; Antonelli, Patrick J.; Dirain, Carolyn O.
Abstract : Objective: Ciprofloxacin, commonly given as eardrops, has been shown to adversely affect tympanic membrane fibroblasts. Dexamethasone potentiates this effect. A newly available eardrop contains ciprofloxacin and fluocinolone, a more potent steroid. We evaluated the cytotoxic effects of this preparation on mouse tympanic membrane fibroblasts. Study Design: Prospective, in vitro. Setting: Academic laboratory. Subjects and Methods: In experiment 1, fibroblasts were exposed to 1:10 dilutions of commercially available 0.3% ofloxacin, 0.3% ciprofloxacin, 0.3% ciprofloxacin + 0.1% dexamethasone, 0.3% ciprofloxacin + 0.025% fluocinolone, or dilute hydrochloric acid (control), twice within 24 hours. In experiment 2, cells were also treated with the dilutions of the pure form of dexamethasone 0.1% or fluocinolone 0.025%, alone and in combination with ofloxacin or ciprofloxacin. Cells were exposed to the solutions for 2 hours each time and were placed back in growth media after the treatments. Cells were observed with phase‐contrast microscope until the cytotoxicity assay was performed. Results: Survival of fibroblasts treated with ofloxacin was not different from the control. Fibroblasts treated with ciprofloxacin, ciprofloxacin + dexamethasone, or ciprofloxacin + fluocinolone had much lower survival (all P <. 0001). Cells treated with ciprofloxacin + fluocinolone had lower survival than ciprofloxacin ( P <. 0001) and ciprofloxacin + dexamethasone ( P =. 0001). Steroids alone also decreased fibroblast survival compared to control ( P <. 0001). The combination of dexamethasone or fluocinolone with ciprofloxacin, but not ofloxacin, further decreased fibroblast survival ( P <. 0001). Phase‐contrast images mirrored the cytotoxicity findings. Conclusion: Tympanic membrane fibroblast cytotoxicity of ciprofloxacin is potentiated by corticosteroids. This effect may be deleterious when treating a healing perforation but beneficial when treating granulation tissue on the tympanic membrane.